A high-concentration NaCl solution does not stimulate the human trigeminal nerve at the tip of the tongue. - Komiyama A; Kobayakawa T; Toda H; Gotow N; Ikeda M; Saito S (Acta Oto-Laryngologica, 2007)
Conclusion. A 3 M NaCl solution does not stimulate the trigeminal nerve in the human tongue. Objectives. In rats, the trigeminal nerve has been reported to respond when the tongue is stimulated by a solution with an NaCl concentration of 0.4 M or greater. We have attempted to clarify whether or not relatively high concentrations of NaCl stimulate the trigeminal nerves of the human tongue. Materials and methods. We examined four patients whose bilateral chorda tympani nerves were resected during middle ear surgeries. We performed subjective tactile and taste tests. Next, we conducted objective examinations of the subjects' tactile and gustatory functions by magnetoencephalography (MEG). Results. The subjective examination confirmed that all four subjects maintained normal tactile sensory functions in their tongues and that the gustatory sensation at their lingual apexes was totally abolished. Furthermore, the objective examination of the tactile function using MEG indicated that their brain responses to trigeminal nerve stimulations were normal. Further examination using MEG failed to produce brain responses to a 3 M NaCl solution in spite of their normally functioning trigeminal nerves. Therefore, we concluded that a 3 M NaCl solution does not stimulate the trigeminal nerve at the tip of the human tongue.